Immunogenicity assessment of biotherapeutic products: An overview of assays and their utility. Issue 5 (September 2015) - Wadhwa, Meenu; Knezevic, Ivana; Kang, Hye-Na; Thorpe, Robin
Abstract Biotherapeutic products (BTPs) are the fastest growing medicines in the pharmaceutical market. Despite their clinical success, the immunogenicity of BTPs continues to be a major concern. Assessment of immunogenicity as well as appropriate interpretation of immunogenicity data is therefore, of critical importance for defining safety profile of these products for the purpose of their licensure and use. In the past decade, much progress has been made towards how immunogenicity should be studied. This article reflects the content of the brief presentation on principles of methods used for immunogenicity assessment and their merits and limitations given at the first World Health Organization (WHO) implementation workshop on rDNA derived biotherapeutic products held in the Republic of Korea in May 2014 to support the case studies on immunogenicity presented and discussed during the workshop. The purpose of this article is to provide an overview of the methods used for assessing immunogenicity of biotherapeutic products (BTPs) and the most important considerations in interpreting results in the context of regulatory overview of these products.